James and Jude : Paideia Commentaries on The New Testament - Painter, John.; Parsons, Mikeal C.; deSilva, David A., 1967-; Parsons, Mikeal C. (Grand Rapids, MI : Baker Academic, 2012)
In this addition to the well-received Paideia series, two respected New Testament scholars offer a practical commentary on James and Jude that is conversant with contemporary scholarship, draws on ancient backgrounds, and attends to the theological nature of the texts. This commentary, like each in the projected eighteen-volume series, proceeds by sense units rather than word-by-word or verse-by-verse. Paideia commentaries explore how New Testament texts form Christian readers by: attending to the ancient narrative and rhetorical strategies the text employs; showing how the text shapes theological convictions and moral habits; commenting on the final, canonical form of each New Testament book; focusing on the cultural, literary, and theological settings of the text; making judicious use of maps, photos, and sidebars in a reader-friendly format. Students, pastors, and other readers will appreciate the historical, literary, and theological insight that John Painter and David deSilva offer in interpreting James and Jude. - Publisher.
Includes bibliographical references (pages 229-238) and index.
Keywords: Bible. -- Commentaries; Bible. -- Commentaries